2013
DOI: 10.1007/s00125-013-3083-x
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal acid lipase and lipophagy are constitutive negative regulators of glucose-stimulated insulin secretion from pancreatic beta cells

Abstract: Aims/hypothesis Lipolytic breakdown of endogenous lipid pools in pancreatic beta cells contributes to glucosestimulated insulin secretion (GSIS) and is thought to be mediated by acute activation of neutral lipases in the amplification pathway. Recently it has been shown in other cell types that endogenous lipid can be metabolised by autophagy, and this lipophagy is catalysed by lysosomal acid lipase (LAL). This study aimed to elucidate a role for LAL and lipophagy in pancreatic beta cells. Methods We employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 48 publications
(74 reference statements)
1
38
0
Order By: Relevance
“…Whether CHOP accumulation under these conditions arises downstream of some (eIF2α), but not all (IRE1α), arms of the unfolded protein response, or as a consequence of the ISR, was not resolved in our studies. Regardless, our data now suggest that suppression of CHOP would represent a beneficial adaptation to high-fat feeding, albeit one that might come at the cost of reduced insulin secretion due to disruption of lipid signalling pathways [9]. Although it is commonly assumed, based on genetic models [12,13], that modulation of ER stress explains the reciprocal relationship between autophagy and beta cell apoptosis [2,4,14], we believe our CHOP data are the first to confirm this mechanistic link in the context of high-fat feeding.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Whether CHOP accumulation under these conditions arises downstream of some (eIF2α), but not all (IRE1α), arms of the unfolded protein response, or as a consequence of the ISR, was not resolved in our studies. Regardless, our data now suggest that suppression of CHOP would represent a beneficial adaptation to high-fat feeding, albeit one that might come at the cost of reduced insulin secretion due to disruption of lipid signalling pathways [9]. Although it is commonly assumed, based on genetic models [12,13], that modulation of ER stress explains the reciprocal relationship between autophagy and beta cell apoptosis [2,4,14], we believe our CHOP data are the first to confirm this mechanistic link in the context of high-fat feeding.…”
Section: Discussionmentioning
confidence: 76%
“…Islet isolation, treatment and immunoblotting Mouse islets were isolated as described previously [9] and then incubated with or without chloroquine (50 μmol/l) for 2 h immediately after isolation. Immunoblotting of islet lysates was as recently described [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous studies (Ong et al 2011; Sapiro et al 2009), overexpressing ATGL increased TAG turnover, but this effect was partially or completely abrogated when autophagy was blunted via exposure of hepatocytes to the autophagy inhibitor chloroquine or knockdown of ATG5 (Figures 3A–B). Moreover, blocking lysosomal lipid hydrolysis, via the lysosomal acid lipase inhibitor LAListat (Pearson et al 2014), prevented the increase in TAG turnover in response to ATGL overexpression (Figure 3C). Consistent with the TAG turnover data, blocking autophagy or lysosomal lipid degradation attenuated the oxidation of hydrolyzed FAs following ATGL overexpression (Figures 3D–F).…”
Section: Resultsmentioning
confidence: 98%
“…It is likely that autophagy functions as a quality control process by eliminating aged secretory granules, and is probably required for the maintenance of beta cell homeostasis. Recently, it was suggested that lysosomal lipid degradation (lipophagy) negatively regulates glucose-stimulated insulin secretion by depletion of substrate for non-lysosomal neutral lipases that regulate insulin secretion [72]. Thus, autophagy-lysosomal degradation may affect both insulin content and secretion.…”
Section: Autophagy In Beta Cell Physiology and Diabetesmentioning
confidence: 99%